Akan-Ewe Christological Constructs: Indigenous Christologies in Post-Missionary Christianity and Theology in Africa - Edward Agboada (E-Journal of Religious and Theological Studies)
The study discussed Akan-Ewe Christological Constructs in Post-Missionary Christianity and Theology in Africa. The objective was to assess their capacity to provide the right frameworks for conceptualising the relevance and significance of Jesus and the gospel in Africa and his Christology. Using the ethnographic and phenomenological approaches, the study established that Akan-Ewe socioreligiocultures and spirituality provide a tapestry of frameworks that offer competitive alternatives to the Christological conceptualisation in post-missionary Christianity and Theology in Africa. The names Onyankopɔn, or Twereduampɔn and Mawu Sogbo Lisa, or Mawu Kitikata for instance, indicate how they conceive, or perceive God (Jesus) who is not a figure of imagination but the “Supreme Being”. He is the first of all, has no equals, the ultimate authority and power over all, and is held in the highest positions in sovereignty, knowledge, and goodness. He is infinitely powerful and superior. The study contributes to the decolonisation of the hegemony of Western/European (Missionary) Christian frameworks for Christianity and Theology in Africa and a search for alternatives that possess the capacity and competitiveness of epistemology or nomenclatures beyond the West/Europe.